2013
DOI: 10.3390/ijms14048406
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Quantitative Trait Loci (QTLs) for Resistances to Small Brown Planthopper and Rice Stripe Virus in Rice Using Recombinant Inbred Lines

Abstract: Small brown planthopper (SBPH) and rice stripe virus (RSV) disease transmitted by SBPH cause serious damage to rice (Oryza sativa L.) in China. In the present study, we screened 312 rice accessions for resistance to SBPH. The indica variety, N22, is highly resistant to SBPH. One hundred and eighty two recombinant inbred lines (RILs) derived from a cross of N22 and the highly susceptible variety, USSR5, were used for quantitative trait locus (QTL) analysis of resistances to SBPH and RSV. In a modified seedbox s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…On the other hand, several resistance QTLs to small brown planthopper (SBPH) have also been reported to be located on chromosomes 1, 2, 3, 4, 7, 11, and 12. Wang et al (2013) compared all known QTLs for their effects against SBPH and concluded that the QTLs located on chromosomes 7, 11, and 12 exert major roles in resistance. Nonetheless, the exact molecular functions of most RSV resistance and/or SBPH resistance QTLs have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several resistance QTLs to small brown planthopper (SBPH) have also been reported to be located on chromosomes 1, 2, 3, 4, 7, 11, and 12. Wang et al (2013) compared all known QTLs for their effects against SBPH and concluded that the QTLs located on chromosomes 7, 11, and 12 exert major roles in resistance. Nonetheless, the exact molecular functions of most RSV resistance and/or SBPH resistance QTLs have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Small brown planthopper transmits virus disease (such as RBSDVD and RSV) and causes a direct damage to the plant. In previous studies, more QTLs against SBPH have been mapped using several populations (Duan et al., , ; Duan, Wan et al., ; Duan, Zhang et al., ; Sun et al., ; Tuyen et al., 2012; Wang et al., ; Zhang et al., ). Compared with these QTLs, qSBPH7 WR24 on chromosome 7 was located in the same interval as qSBPH7 .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with these QTLs, qSBPH7 WR24 on chromosome 7 was located in the same interval as qSBPH7 . It is noteworthy that qSBPH7 has been repeatedly detected by three different phenotypic methods from a SBPH resistance cultivar N22 (Wang et al., ), suggesting qSBPH7 WR24 will be a reliable QTL for SBPH resistance breeding. Except qSBPH7 WR24 , the other two SBPH resistance QTLs, viz.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations